Obesity-Related Chronic Kidney Disease: Principal Mechanisms and New Approaches in Nutritional Management - Stasi, Alessandra; Cosola, Carmela; Caggiano, Gianvito; Cimmarusti, Maria Teresa; Palieri, Rita; Acquaviva, Paola Maria; Rana, Gloria; Gesualdo, Loreto (Frontiers in Nutrition, 2022)
Obesity is the epidemic of our era and its incidence is supposed to increase by more than 30% by 2030. It is commonly defined as a chronic and metabolic disease with an excessive accumulation of body fat in relation to fat-free mass, both in terms of quantity and distribution at specific points on the body. The effects of obesity have an important impact on different clinical areas, particularly endocrinology, cardiology, and nephrology. Indeed, increased rates of obesity have been associated with increased risk of cardiovascular disease (CVD), cancer, type 2 diabetes (T2D), dyslipidemia, hypertension, renal diseases, and neurocognitive impairment. Obesity-related chronic kidney disease (CKD) has been ascribed to intrarenal fat accumulation along the proximal tubule, glomeruli, renal sinus, and around the kidney capsule, and to hemodynamic changes with hyperfiltration, albuminuria, and impaired glomerular filtration rate. In addition, hypertension, dyslipidemia, and diabetes, which arise as a consequence of overweight, contribute to amplifying renal dysfunction in both the native and transplanted kidney. Overall, several mechanisms are closely related to the onset and progression of CKD in the general population, including changes in renal hemodynamics, neurohumoral pathways, renal adiposity, local and systemic inflammation, dysbiosis of microbiota, insulin resistance, and fibrotic process. Unfortunately, there are no clinical practice guidelines for the management of patients with obesity-related CKD. Therefore, dietary management is based on the clinical practice guidelines for the nutritional care of adults with CKD, developed and published by the National Kidney Foundation, Kidney Disease Outcome Quality Initiative and common recommendations for the healthy population. Optimal nutritional management of these patients should follow the guidelines of the Mediterranean diet, which is known to be associated with a lower incidence of CVD and beneficial effects on chronic diseases such as diabetes, obesity, and cognitive health. Mediterranean-style diets are often unsuccessful in promoting efficient weight loss, especially in patients with altered glucose metabolism. For this purpose, this review also discusses the use of non-classical weight loss approaches in CKD, including intermittent fasting and ketogenic diet to contrast the onset and progression of obesity-related CKD.